Notes on the genus Rasilinus Mazur, 2016 (Curculionidae: Curculioninae, Eugnomini), with the description of a new species from New Caledonia - Mazur, Miłosz A. (Zootaxa, 2017)
New data on the genus Rasilinus (Curculioninae, Eugnomini) are provided, including the description of a new species—Rasilinus bifasciatus sp. n., from New Caledonia. Illustrations and SEM photographs of male external morphology, terminalia, and a colour habitus of the adult of the new species are provided.